Omission of a carbohydrate-rich breakfast impairs evening endurance exercise performance despite complete dietary compensation at lunch - Richard Metcalfe (European Journal of Sport Science, 2021)
Omission of a carbohydrate-rich breakfast followed by consuming an ad libitum lunch impairs evening exercise performance. However, it is unclear if this is due to breakfast omission per se, or secondary to lower carbohydrate intake over the day. To test whether impaired evening performance following breakfast omission persists when complete dietary compensation occurs at lunch, in a randomised cross-over design, eleven highly trained cyclists (age: 25 ± 7 y, VO2max: 61 ± 5 ml·kg-1·min-1) completed two trials: breakfast (B) and no breakfast (NB). During B, participants consumed an individualised breakfast (583±54 kcal; 8-9am) and lunch (874±80 kcal; 12-2pm), whilst during NB participants fasted until 12pm and then consumed a standardised lunch (1457±134 kcal: 12-2pm). The overall energy (1457±134 kcal) and macronutrient profile (carbohydrate: 81.5±0.4%, fat: 5.8±0.1%, protein: 12.7±0.3%) was identical in both trials, with timing the only difference. Mean power output during a 20 km time trial performed in the evening was ∼3% lower in NB compared to B (mean difference [95% CI]: -9.1 [-15.3, -2.9] watts, p<0.01 for condition main effect). No differences in heart rate, blood glucose or blood lactate concentrations were apparent, but perception of effort appeared to be higher in the early stages of the time trial in NB compared to B despite lower power output. Impaired high-intensity endurance performance in the evening following breakfast omission is related to meal timing rather than carbohydrate intake / availability. Provision of an early morning high-carbohydrate meal should be considered to optimise evening exercise performance.